INCREASING MOTIVATION IN PHYSICAL EDUCATION CLASSES AT AN AGRARIAN UNIVERSITY - Petrenko Natalia (Borys Grinchenko Kyiv Metropolitan University, 2020)
This article defines the criteria for the formation of the pedagogical competence of scientific and pedagogical workers in physical education (motivational-value, cognitive-processual, developmental, educational, health-saving, communicative), their structure, content and measurement methods are disclosed. The determination of the components of the pedagogical competence of scientific and pedagogical workers of physical education makes it possible to significantly expand the range of pedagogical knowledge, skills and abilities of scientific and pedagogical workers of physical education, as well as to carry out their diagnostics as a kind of reference point for the content of the methodological work of the model of the educational process, which will help to adjust the process of development of pedagogical competence scientific and pedagogical workers of physical education in the methodological work of an agricultural university. Physical education in an agrarian institution of higher education is aimed at solving the following specific tasks: formation of high moral, strong-willed and physical qualities of the learners of higher education, readiness for highly productive work; students' health protection and promotion, promotion the all-round development of the body, maintaining high performance throughout the study period; comprehensive physical training; vocational-applied physical training of higher education learners, taking into account the features of future employment; gaining the necessary knowledge of the fundamentals of theory, methodology, and organization of physical education and sports training, preparation for work as public instructors, coaches and judges; improving the athletic skills of higher education athletes; nurturing awareness of the need to regularly exercise in physical culture and sports